Urgensi Penegakan Hukum Pajak dalam Meningkatkan Kepatuhan Wajib Pajak di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The implementation of tax law has a crucial position in improving tax compliance and maintaining the stability of state finances. In Indonesia, although there is an adequate legal basis, the implementation of tax law still faces a number of problems such as violations of supervision, inefficient sanctions, and low understanding of taxation. This study aims to analyze ideas for the implementation of tax law, identify taxpayer conditions, and disseminate the effectiveness of law implementation in order to build a fair and sustainable taxation system. The method used is a literature review with a juridical-normative approach. The results of the study show that the success of law implementation is greatly influenced by regulations, human resources, information technology, and political commitment and cooperation between institutions. Therefore, a comprehensive strategy is needed in the form of regulatory reform, digitalization of supervision, improving the quality of human resources, and public education so that tax compliance can increase significantly and sustainably.